DISTRIBUTION PATTERN OF NEUROENZYME ACETYLCHOLINESTERASE IN THE OLFACTORY BULB OF AN INDIAN AIR BREATHING TELEOST CHANNA PUNCTATUS - MATIUR RAHMAN; ANURAG TRIPATHI (The Bioscan, 2013)
The present work deals with the histoenzymological distribution pattern of enzyme acetylcholinesterase (E.C.3.1.1.7) in the different layers of olfactory bulb of Channa punctatus by employing a modified technique to visualize acetylcholinesterase containing neurons. Acetylcholinesterases distribution in the olfactory bulb shows a precise laminar distribution of enzyme which is alternatively mild, strong, weak or negative in the different layers. Layers with maximum enzyme reaction most likely correspond to areas with prevalence of cholinergic mechanism, whereas layers with mild or negative reaction may be considered to be non cholinergic/cholinoceptive.